Metal component with low coefficient of thermal expansion and high mechanical strength
By precipitating the γ" (second γ) phase in the iron-based alloy and adjusting the Nb and Ni elements, combined with appropriate heat treatment and physical treatment, the problem that Fe-Ni alloys in the prior art is difficult to take into account both low CTE and high mechanical strength in additive manufacturing, and the consideration of low CTE and high mechanical strength of the alloy at high temperature is achieved.
Patent Information
- Application Number
- CN202380062358.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-07-28
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to use Fe-Ni alloys for additive manufacturing while maintaining low coefficient of thermal expansion (CTE) and increasing mechanical strength.
By precipitating the γ" (second γ) phase in the iron-based alloy, adjusting the content of Nb and Ni elements, combined with appropriate heat treatment and physical treatment, the hardness and mechanical strength of the alloy are improved while controlling CTE.
The alloy has both low CTE and high mechanical strength at temperatures up to about 200°C, suitable for additive manufacturing and manufacturing of metal parts of rubber products.
Smart Images

Figure BDA0005287688940000161 
Figure BDA0005287688940000191
Abstract
Description
Technical Field
[0001] The present invention relates to metal parts based on iron, in particular Fe-Ni alloys, intended for the manufacture of rubber articles, such as wheel tires, tracks, conveyor belts or drive belts, and the manufacture of such parts, said metal parts having a low isobaric coefficient of thermal expansion for temperatures up to about 200° C. A common term is the coefficient of thermal expansion (CTE). Background Art
[0002] The metal parts used for the manufacture of pneumatic or non-pneumatic tires, rubber tracks, vehicle wheels (i.e. having a mobile function) and / or parts of pneumatic or non-pneumatic tires, rubber tracks or such wheels must meet many requirements, in particular good mechanical strength in order not to deform during use and thus ensure an acceptable service life, and thermal expansion as low as possible, in order to control the geometry of the rubber object formed. As a reminder, the term "pneumatic tire" refers to a tire capable of supporting a load (e.g. a vehicle) by means of pressurized gas. The term "non-pneumatic tire" refers to a tire capable of supporting a load (e.g. a vehicle) by means other than pressurized gas, for example by guy wires.
[0003] For example, a sector-shaped curing mold or a vulcanizing mold for a vehicle wheel tire mainly comprises two shells and a plurality of sectors, each shell molding a sidewall of the tire, and the plurality of sectors molding the tread of the tire, and can move radially between the open position and the closed position of the mold. The shell and the sectors define an inner space, and the inner space is intended to contact with the unvulcanized tire blank. In order to form a tread pattern, a strip is attached to the mold sector and protrudes into the inner space. For more details of the mold comprising these strips, reference may be made to, for example, EP 1758743 and US2002 / 0139164.
[0004] Not only must these components have sufficient mechanical strength to not break during use and to withstand the stresses associated with shaping the molded materials, but they must also deform as little as possible during the temperature cycles associated with the curing (or cross-linking) of these materials.
[0005] The main advantage of manufacturing by selective fusion of superimposed powder layers (more commonly known as "powder bed fusion") is that this technology is well suited to the manufacture of small, complex-shaped components (such as mold trim strips) that are difficult to manufacture by other processes.
[0006] When selective melting is performed using a laser beam, when the powder particles are partially melted, the process is called sintering, or laser melting. The laser melting technique consists in making a strip layer by layer by stacking powder layers that are consolidated and melted to each other along the stacking direction using a laser beam. The term "powder" means a powder or a mixture of powders (which are mainly metals, but can also be minerals, such as ceramics).
[0007] The first layer is deposited on the build plate and then melted directly. The other layers are then formed in sequence, so that a stack is obtained starting from the first layer.
[0008] Typically, the manufacture of smaller elements, such as decorative strips, is carried out horizontally on the manufacturing plate, so that its length is substantially parallel to the manufacturing plate. This is called horizontal manufacturing. This avoids having too high a strip height, thus reducing manufacturing time. Such elements must have good fracture strength and / or fatigue strength properties to ensure a long service life, so the alloys used in such manufacturing are crucial.
[0009] In the prior art, Fe-Ni alloys of composition generally of the type 64Fe-36Ni are known which have a low coefficient of thermal expansion for temperatures up to about 200°C. They are generally known under the name 36 sales. However, it would be advantageous to increase the mechanical strength and hardness of such alloys while keeping the coefficient of thermal expansion (CTE) as low as possible and allowing them to be used in additive manufacturing.
[0010] It is known to strengthen alloys by precipitation of various carbides and intensive deformation (especially when cold) to increase the 36 mechanical strength.
[0011] This is the case of patent application WO 03 / 025239, which proposes strengthening with Ti, Nb, V, Mo, Hf and Ta carbides and producing extremely cold deformed wire. -6 / ° C, the authors obtained tensile strengths Rm up to 1300 MPa. However, the alloys thus obtained cannot be used for additive manufacturing because their carbon content is too high and the presence of carbides therefore hinders said additive manufacturing.
[0012] This is also the case with patent application RU 2568541, which also proposes strengthening with large amounts of carbides of Nb, Ti, V, Mo, W and Zr. Thus, after forging and heat treatment, the CTE is <7×10 -6 / ° C, the authors obtained a tensile strength Rm of up to 1900 MPa. However, due to the presence of cobalt (for health and safety reasons, cobalt should be removed from the powder and its content does not exceed 0.5 wt.%), the alloy thus obtained cannot be used for additive manufacturing.
[0013] Nakama et al. (Metallogr. Microstruct. Anal. 2, 383-387 (2013)) also proposed strengthening by precipitation of V or Ti or Zr or Nb or Ta carbides. After forging and heat treatment, for 2.5x10 -6 / ° C, the authors obtained tensile strengths Rm up to 1010 MPa. However, the alloys thus obtained cannot be used for additive manufacturing because their carbon content is too high, which is hindered by the presence of carbides.
[0014] The inventors unexpectedly realized that it is possible to increase the mechanical strength of mechanical parts while keeping the CTE as low as possible and allowing them to be manufactured by additive manufacturing. Therefore, the inventors realized that in order to obtain such a result (Rm-CTE compromise), it is necessary to adjust the Nb and Ni elements simultaneously to carry out hardening by precipitation of the γ" (second γ) phase of the alloy. In particular, fine intragranular precipitates are thereby obtained, which disturb the magnetic order less than larger precipitates and therefore increase the CTE less. The heat treatment after additive manufacturing can also be simplified by not dissolving at very high temperatures to obtain the required hardening. In addition, all the additional Nb and Ni elements are present in the precipitates, without any remaining in solid solution in the austenite, which would be detrimental to the CTE, and after precipitation of all possible γ" (second γ) phases, 36% of the Ni in the austenite is still replaced, thus being in the best CTE conditions. Carbon is also added to the composition to form a small amount of NbC carbides so that the austenite grain growth is limited during heat treatment. However, the carbon content is limited so that it can be used for additive manufacturing. Summary of the invention
[0015] Detailed description of the invention
[0016] The present invention relates to a metal part for the manufacture of rubber products based on an iron-based alloy composition comprising (advantageously consisting essentially of), in percentage by weight of all the components:
[0017] Nickel: 38.0-42.0, advantageously 39.0-42.0;
[0018] Niobium: 4.750-5.500, advantageously 5.000-5.500;
[0019] Carbon: 0.010-0.100, advantageously 0.015-0.070;
[0020] Cobalt: ≤ 0.400, advantageously ≤ 0.100;
[0021] Chromium: ≤0.500;
[0022] Silicon: ≤0.500;
[0023] Manganese: ≤0.500;
[0024] Iron: balance;
[0025] and inevitable impurities.
[0026] The invention also relates to a method for producing such a metal component, said method comprising the following steps:
[0027] A- An iron-based alloy powder having the components of the alloy composition on which the metal part according to the invention is based is produced according to the following steps:
[0028] a) mixing basic starting materials or pre-alloying starting materials;
[0029] b) melting the mixture obtained in step a), advantageously in a vacuum induction muffle furnace;
[0030] c) atomizing the product obtained in step b) (advantageously using nitrogen) to obtain a powder;
[0031] d) screening or sieving the powder obtained in step c) to obtain a desired particle size fraction;
[0032] e) recovering the powder obtained.
[0033] B1-subjecting the powder obtained in step A) to an additive manufacturing process or hot isostatic pressing to obtain the component, the additive manufacturing process advantageously being selected from powder bed selective laser melting (LBM), electron beam melting (EBM), powder spray laser melting (such as direct additive laser structuring or direct metal deposition (DMD)) and binder injection on a powder bed (MBJ), or
[0034] B2—subjecting the powder obtained in step A) to a laser melting process by powder spraying (e.g. direct additive laser structuring or direct metal deposition (DMD)) and then forging the deposit formed from the melted powder,
[0035] C- subjecting the part obtained in step B1) or step B2) to at least one thermal and / or physical and / or chemical treatment, advantageously chosen from a relaxation heat treatment, a hot isostatic pressing treatment (if step B1) is not a hot isostatic pressing treatment), a dissolution treatment, an aging treatment, a finishing treatment (for example a surface modification treatment or the deposition of a coating to prevent corrosion and oxidation) and combinations of these treatments,
[0036] D- Recover the components thus obtained.
[0037] The invention also relates to a method for producing such a metal component, said method comprising the following steps:
[0038] i. Mixed base starting materials or pre-alloyed starting materials;
[0039] ii. melting the mixture obtained in step i), advantageously in a vacuum induction muffle furnace,
[0040] iii. optionally, homogenizing by heat treating the ingot obtained in step ii),
[0041] iv. transforming the ingot obtained in any one of steps ii) and iii) by forging,
[0042] v. Recycling of the components thus obtained,
[0043] vi. Preferably, the part obtained in step v) is subjected to at least one thermal and / or physical and / or chemical treatment, which is advantageously selected from a relaxation heat treatment, a hot isostatic pressing treatment, a solution treatment, an aging treatment, a finishing treatment (such as a surface modification treatment or deposition of a coating to prevent corrosion and oxidation) and a combination of these treatments.
[0044] The invention also relates to a metal part obtained by one of these methods, and to the use of a metal part according to the invention or of a metal part obtained by a method according to the invention for the manufacture of pneumatic or non-pneumatic tires, rubber tracks, vehicle wheels (i.e. having a mobile function) and / or parts of pneumatic or non-pneumatic tires, rubber tracks or such wheels.
[0045] definition
[0046] Herein, unless otherwise expressly stated, all percentages (%) shown are mass percentages (%).
[0047] The expression "composition based on" is understood to mean that the composition comprises a mixture and / or in situ reaction products of the various components used, some of which are able and / or intended to react at least partially with one another during the various manufacturing stages of the composition. In the more specific case of a rubber composition, the composition can thus be in a completely crosslinked state or in a partially crosslinked state or in a non-crosslinked state.
[0048] The carbon-containing compounds mentioned in the specification may be compounds of fossil origin or bio-based origin. In the case of compounds of bio-based origin, they may be partially or completely derived from biomass, or may be obtained from renewable starting materials derived from biomass. In particular, they relate to polymers, plasticizers, fillers, etc.
[0049] Metal parts
[0050] The present invention therefore relates to a metal part for the manufacture of rubber products based on an iron-based alloy composition comprising (advantageously essentially consisting of, in particular consisting of), in percentage by weight of all the components:
[0051] Nickel: 38.0-42.0, advantageously 39.0-42.0;
[0052] Niobium: 4.750-5.500, advantageously 5.000-5.500;
[0053] Carbon: 0.010-0.100, advantageously 0.015-0.070;
[0054] Cobalt: ≤ 0.400, advantageously ≤ 0.100;
[0055] Chromium: ≤0.500;
[0056] Silicon: ≤0.500;
[0057] Manganese: ≤0.500;
[0058] Iron: balance;
[0059] and inevitable impurities.
[0060] The metal part based on a particularly advantageous iron-based alloy composition for producing a rubber article according to the invention comprises (advantageously essentially consists of, in particular consists of), in terms of percentage by weight of all components:
[0061] Nickel: 39.0-42.0;
[0062] Niobium: 5.000-5.500;
[0063] Carbon: 0.015-0.070;
[0064] Cobalt: ≤0.050;
[0065] Chromium: ≤0.100;
[0066] Silicon: ≤0.500;
[0067] Manganese: ≤0.500;
[0068] Iron: balance;
[0069] and inevitable impurities.
[0070] In the context of the present invention, the ranges “X % to Y %” and “X to Y” are meant to include the limits X and Y. The range “between X and Y” does not include the limits X and Y.
[0071] The measurement uncertainties shown are typical uncertainties in the context of the present invention.
[0072] In particular, unavoidable impurities, in particular selected from nitrogen (N), oxygen (O), hydrogen (H), sulfur (S), phosphorus (P), aluminum (Al), titanium (Ti), vanadium (V), molybdenum (Mo), calcium (Ca), copper (Cu), magnesium (Mg) and mixtures thereof, are kept as low as possible. These impurities are generally caused essentially by the manufacturing process and the quality of the charge. Advantageously, the alloy composition on which the metal part according to the invention is based contains not more than 1.00% by weight, advantageously not more than 0.75% by weight, even more advantageously not more than 0.50% by weight of unavoidable impurities relative to the total weight of the composition. In general, the content of impurities in the alloy is measured with an absolute uncertainty of ± 0.08%.
[0073] In particular, the alloy composition on which the metal part according to the invention is based comprises, in percentage by weight of all components:
[0074] Nitrogen ≤ 0.030, advantageously ≤ 0.020, in particular ≤ 0.010, and / or
[0075] Oxygen ≤ 0.040, advantageously ≤ 0.035.
[0076] Limiting the nitrogen content can limit the formation of nitrides in the alloy, which can be detrimental to the CTE. The nitrogen content is measured with an absolute uncertainty of ±0.0012%.
[0077] Limiting the oxygen content limits the formation of oxides which can be detrimental to the CTE and ductility of the alloy. Oxygen contents of this magnitude may appear surprising compared to conventional processes, but sorting metals in powder form produces very high surface area / volume ratios which will significantly increase the oxygen content of the alloy. This will increase further if the powder manufacturing process is not adequately controlled. The oxygen content is measured with an absolute uncertainty of ±0.0019%.
[0078] Advantageously, the alloy composition on which the metal part according to the invention is based has a hydrogen content of ≤ 0.0050% by weight relative to the total weight. Limiting the hydrogen content makes it possible to limit the embrittlement of the alloy. The hydrogen content is measured with an absolute uncertainty of ± 0.0005%.
[0079] Advantageously, the alloy composition on which the metal part according to the invention is based has a sulfur content of ≤0.0150% by weight of the total components, advantageously ≤0.0050% by weight of the total components. Limiting the sulfur content makes it possible to limit the formation of low-melting phases (such as FeS) which wet the grain nodes, which is detrimental to the alloy. In particular, the mechanical strength of these phases is very low, so their presence reduces the mechanical properties of the alloy. The sulfur content is measured with an absolute uncertainty of ±0.0001%.
[0080] Advantageously, the alloy composition on which the metal part according to the invention is based has a phosphorus content of ≤0.0150% by weight of the total components, advantageously ≤0.0050% by weight of the total components. Limiting the phosphorus content makes it possible to limit the formation of low-melting phases (such as Fe3P) which can accumulate in the grain nodes and thus be detrimental to the alloy by reducing its resilience. The phosphorus content is measured with an absolute uncertainty of ±0.0001%.
[0081] Advantageously, the alloy composition on which the metal part according to the invention is based has an aluminum content of ≤ 0.100% by weight of the total components. Limiting the aluminum content makes it possible to limit the formation of any intermetallic phases between Ni and Al, such as the γ' (first gamma) phase, which will lead to the formation of precipitates that may be larger than the γ" (second gamma) precipitates and will reduce the Ni content in the austenite. This will therefore lead to an increase in the CTE. The aluminum content is measured with an absolute uncertainty of ± 0.005%.
[0082] Advantageously, the alloy composition on which the metal part according to the invention is based has a titanium content of ≤ 0.100% by weight of the total components. Limiting the titanium content makes it possible to limit the formation of any intermetallic phases between Ni and Ti, such as the γ' (first gamma) phase or the η (eta) phase, which would lead to the formation of precipitates that could be larger than the γ" (second gamma) precipitates and would reduce the Ni content in the austenite. This would therefore lead to an increase in the CTE. The titanium content is measured with an absolute uncertainty of ± 0.005%.
[0083] Advantageously, the alloy composition on which the metal part according to the invention is based has a vanadium content of ≤ 0.100% by weight of all the components. Limiting the vanadium content makes it possible to limit the formation of coarse vanadium carbides which can adversely affect the CTE. The vanadium content is measured with an absolute uncertainty of ± 0.007%.
[0084] Advantageously, the alloy composition on which the metal part according to the invention is based has a molybdenum content of ≤ 0.020% by weight of the total components. Limiting the molybdenum content makes it possible to limit the formation of coarse molybdenum carbides, which can have a negative effect on the CTE. The molybdenum content is measured with an absolute uncertainty of ± 0.003%.
[0085] Advantageously, the alloy composition on which the metal part according to the invention is based has a calcium content of ≤ 0.015% by weight of the total components. Limiting the calcium content makes it possible to limit the formation of inclusions that are detrimental to the alloy. The calcium content is measured with an absolute uncertainty of ± 0.005%.
[0086] Advantageously, the copper content of the alloy composition on which the metal part according to the invention is based is ≤ 0.010% by weight of the total components. Limiting the copper content makes it possible to limit the formation of copper precipitates in the grain nodes, which may be detrimental to the CTE and to the mechanical properties of the alloy. The copper content is measured with an absolute uncertainty of ± 0.002%.
[0087] Advantageously, the alloy composition on which the metal part according to the invention is based has a magnesium content of ≤0.015% by weight of the total components. Limiting the magnesium content makes it possible to limit the formation of inclusions that are detrimental to the alloy. The magnesium content is measured with an absolute uncertainty of ±0.005%.
[0088] Preferably, the alloy composition on which the metal part according to the present invention is based has a content of unavoidable impurities selected from nitrogen (N), oxygen (O), hydrogen (H), sulfur (S), phosphorus (P), aluminum (Al), titanium (Ti), vanadium (V), molybdenum (Mo), calcium (Ca), copper (Cu), magnesium (Mg) and mixtures thereof that satisfies at least one of the following conditions, preferably at least two, more preferably at least three, and most preferably all:
[0089] Nitrogen ≤ 0.030 wt% of all components;
[0090] Oxygen ≤ 0.040 wt% of all components;
[0091] Hydrogen ≤ 0.0050 wt% of all components;
[0092] Sulfur ≤ 0.0150 wt% of all components;
[0093] Phosphorus ≤ 0.0150 wt% of all components;
[0094] Aluminum ≤ 0.100% by weight of all components;
[0095] Titanium ≤ 0.100 wt% of all components;
[0096] Vanadium ≤ 0.100 wt% of all components;
[0097] Molybdenum ≤ 0.020 wt% of all components;
[0098] Calcium ≤ 0.015% by weight of all components;
[0099] Copper ≤ 0.010 wt% of all components;
[0100] Magnesium ≤ 0.015 wt% of the total components.
[0101] The alloy composition on which the metal part according to the invention is based therefore contains nickel (Ni) in a content of weight percentage ranging from 38.0 to 42.0, advantageously from 39.0 to 42.0, even more advantageously from 39.5 to 42.0, relative to the total weight of the composition. Specifically, nickel plays two roles in the alloy: the first is to give the alloy Invar properties (i.e. low CTE up to about 200°C), and the second is to participate in the hardening of the alloy by forming γ" (second gamma) or δ (delta) precipitates, both of which have a Ni3Nb composition. A minimum nickel content of 38.0% is required to keep 36% of Ni substitutions in the austenite after all possible γ" (second gamma) phase precipitations in order to be in optimal CTE conditions. It is undesirable to exceed a Ni content of 42% because then there are too many Ni substitutions in the matrix, which will be detrimental to the CTE. The nickel content is measured with an absolute uncertainty of ±0.3%.
[0102] The alloy composition on which the metal part according to the invention is based therefore also contains niobium (Nb) in a content ranging from 4.750 to 5.500, advantageously from 5.000 to 5.500 and even more advantageously from 5.100 to 5.300 by weight relative to the total weight of the composition. In particular, niobium mainly allows the formation of small precipitations of the hardening phase γ" (second gamma) in the intergranular space, which is very compatible with additive manufacturing, since it does not create cracking problems, and with the desired applications, since it does not significantly increase the CTE. Niobium also allows the formation of a small fraction of carbides of Nb, which keep the grains together during heat treatments, in particular during dissolution. The Nb content must be greater than 4.750 to obtain the desired strengthening. On the other hand, it is undesirable to exceed 5.500, since this would significantly reduce the CTE and could lead to the precipitation of undesirable phases. The niobium content is measured with an absolute uncertainty of ± 0.005%.
[0103] The alloy composition on which the metal part according to the invention is based also contains carbon (C), whose weight percentage content ranges from 0.010 to 0.100, advantageously from 0.015 to 0.070, even more advantageously from 0.015 to 0.050, relative to the total weight of the composition. In particular, carbon allows the precipitation of Nb carbides at high temperatures, which hinder grain growth during heat treatment (especially during dissolution). In order to obtain high hardening and high yield strength, grain growth must be controlled. The carbon content must be less than 0.100 to enable additive manufacturing. At this content, the carbon is located in the precipitates, rather than remaining in a solid solution in austenite (which would be detrimental to CTE). The measured carbon content has an absolute uncertainty of ± 0.0015%.
[0104] The cobalt (Co) content of the alloy composition on which the metal part according to the present invention is based is ≤0.400 wt. %, advantageously ≤0.100 wt. %, more advantageously ≤0.050 wt. % relative to the total weight of the composition. In particular, the cobalt content must be as low as possible, because cobalt can cause HSE (health, safety, environment) problems when processing powders produced by additive manufacturing. In an advantageous embodiment, the alloy composition on which the metal part is based contains only cobalt as an unavoidable impurity. The term "containing only cobalt as an unavoidable impurity" means that the cobalt content is as low as possible, preferably less than or equal to the measurement tolerance. Therefore, the alloy composition on which the metal part according to the present invention is based can be said to be "free of" cobalt. The measured cobalt content has an absolute uncertainty of ± 0.003%.
[0105] The alloy composition on which the metal part according to the invention is based has a chromium (Cr) content of ≤ 0.500% by weight relative to the total weight of the composition, advantageously ≤ 0.100% by weight relative to the total weight of the composition. In particular, the chromium content must be as low as possible, since chromium may form carbides or become a solid substitute in austenite during heat treatment, which would be detrimental to the CTE. The chromium content is measured with an absolute uncertainty of ± 0.0015%.
[0106] The alloy composition on which the metal part according to the invention is based has a silicon (Si) content of ≤ 0.500% by weight relative to the total weight of the composition, advantageously ≤ 0.470% by weight relative to the total weight of the composition. In particular, the silicon content must be as low as possible, since this element is known to segregate in liquids, leading to the formation of oxides or low-melting phases, which can cause problems for use in additive manufacturing, such as cracking. The silicon content is measured with an absolute uncertainty of ± 0.0063%.
[0107] The alloy composition on which the metal part according to the invention is based has a manganese (Mn) content of ≤ 0.500 wt. % relative to the total weight of the composition, advantageously ≤ 0.400 wt. % relative to the total weight of the composition. In particular, the manganese content must be as low as possible, since this element may induce the formation of oxides or carbides that are detrimental to the CTE. The manganese content is measured with an absolute uncertainty of ± 0.009%.
[0108] In particular, the alloy composition on which the metal part according to the invention is based may be selected from one of the two examples shown in Table 1 and Table 3 of the Examples section below.
[0109] The metal part according to the invention may be manufactured from an iron-based alloy composition in the form of a powder, a forged part, a rolled part or a wire, advantageously a powder (particularly intended for additive manufacturing) or a forged part.
[0110] In an advantageous embodiment, the metal part according to the invention can be manufactured from the alloy composition in the form of a wire (for use in the form of a wire) or in the form of a cable formed from the wire or intended for forming by wire deposition, according to the various possible processes (arc, plasma, electron beam or laser).
[0111] In another advantageous embodiment, the metal part according to the invention can be manufactured from the alloy composition in powder form, intended for shaping by additive manufacturing, advantageously selected from powder bed selective laser melting (LBM), electron beam melting (EBM), powder spray laser melting (e.g. direct additive laser structuring) or direct metal deposition (DMD)) and metal binder jetting (MBJ), more particularly selected from powder bed selective laser melting (LBM).
[0112] The metal part according to the invention is preferably based on a powder having a particle size distribution (number diameter) in the range of 10 μm to 60 μm, in particular if it is intended for the manufacture of parts by powder bed selective laser melting (LBM). Traditionally, for this type of particle size cut, the lower limit of 10 μm (characterized by the number D10) is controlled by laser diffraction (ASTM B822-17) and the upper limit of 60 μm (characterized by the number D90) is controlled by screening. According to the standard ASTM B214-16 or ISO2591-1, which came into force in 1988, the practice of particle size cut control allows the cut up to 45 μm to be controlled by screening. Below this limit, screening control according to the standard is no longer allowed and is characterized by the D10 value of the distribution number measured by laser diffraction.
[0113] The metal part according to the invention is preferably selected from curing moulds, injection moulds and the constituent elements of these moulds. In particular, its mechanical properties make it particularly suitable for these uses which are subjected to multiple heating / cooling cycles.
[0114] Manufacturing method
[0115] The present invention also relates to a method for producing a metal component for producing a rubber product according to the present invention from an iron-based alloy, the method comprising the following steps:
[0116] A-Manufacturing an iron-based alloy powder having the composition of the alloy composition on which the metal part according to the invention is based, is advantageously manufactured by the following process:
[0117] a- mixed basic starting materials or pre-alloyed starting materials,
[0118] b- melting the mixture obtained in step a), advantageously in a vacuum induction muffle (VIM) furnace,
[0119] c- atomizing the product obtained in step b) (advantageously using nitrogen) so as to obtain a powder which is advantageously predominantly spherical (ie without any sharp angles),
[0120] d- screening or sieving the powder obtained in step c) (advantageously under an inert atmosphere) to obtain the desired particle size fraction,
[0121] e- Recover the powder obtained.
[0122] Therefore, the particle size of the powder is adjusted according to the envisaged additive manufacturing technology or powder deposition process. The particle size range for various additive manufacturing or powder deposition processes varies according to the technology, equipment and intended application. In general, if all applications are combined, the powders used for these processes will have a more or less wide particle size distribution with a number between 5 μm and 150 μm (as mentioned above, the lower limit of 5 μm (characterized by the number D10) is controlled by laser diffraction (ASTM B822-17), and the upper limit of 150 μm (characterized by the number D90) is controlled by screening).
[0123] B1-subjecting the powder obtained in step A) to an additive manufacturing process or hot isostatic pressing (HIC) to obtain a component, wherein the additive manufacturing process is advantageously selected from powder bed selective laser melting (LBM), electron beam melting (EBM), powder spray laser melting (e.g. direct additive laser structuring) or direct metal deposition (DMD) and binder injection on powder bed (MBJ), or
[0124] B2 - Direct additive laser structuring by powder coating (e.g. or direct metal deposition (DMD)) subjecting the powder obtained in step A) to a laser melting process, and then forging the deposit formed from the melted powder,
[0125] C- subjecting the part obtained in step B1) or step B2) to at least one thermal and / or physical and / or chemical treatment, advantageously chosen from a relaxation heat treatment, a hot isostatic pressing (HIC) treatment (if step B1) is not a hot isostatic pressing (HIC) treatment), a dissolution treatment, an aging treatment, a finishing treatment (for example a surface modification treatment or the deposition of a coating to prevent corrosion and oxidation) and combinations of these treatments,
[0126] D- Recover the components thus obtained.
[0127] Additive manufacturing processes that can be used in the context of the present invention (such as, in particular, powder bed selective laser melting (LBM), electron beam melting (EBM), powder spray laser melting (such as direct additive laser structuring) Or direct metal deposition (DMD)) and powder bed binder injection (MBJ)) are well known to those skilled in the art.
[0128] In an advantageous embodiment, step B1) comprises an additive manufacturing process which consists in manufacturing the component layer by layer using an energy source (laser beam or electron beam) which melts a thin layer of a high-temperature alloy powder according to the invention. A second layer of a high-temperature alloy powder according to the invention is then deposited and melted. This process is repeated until the final component is obtained. Advantageously, this is powder bed selective laser melting (LBM).
[0129] In an advantageous embodiment, step C) of the method of the invention comprises a dissolution treatment at between 1050° C. and 1150° C., advantageously between 1050° C. and 1100° C., in particular at 1050° C., for 1 to 4 hours, advantageously for 1 hour, followed by an aging treatment at between 600° C. and 700° C., advantageously between 600° C. and 650° C., in particular at 600° C., for 5 to 10 hours, advantageously for 5 hours, or a direct aging treatment at between 600° C. and 700° C., advantageously between 600° C. and 650° C., in particular at 600° C., for 5 to 10 hours, advantageously for 5 hours, without dissolution. Such treatment conditions make it possible to maximize the hardness of the metal part.
[0130] In a particularly advantageous embodiment, step C) of the method according to the invention comprises a direct ageing treatment at between 600° C. and 700° C., advantageously between 600° C. and 650° C., in particular at 600° C., for 5 to 10 hours, advantageously for 5 hours, without dissolution. Such treatment conditions make it possible to maximize the hardness of the metal part if a high-temperature heat treatment is not desired.
[0131] In another advantageous embodiment, step C) of the method according to the invention comprises a dissolution treatment at 900° C. to 1000° C., advantageously 900° C. to 950° C., in particular at 950° C., for 30 minutes to 1 hour, followed by an aging treatment at 600° C. to 700° C., advantageously 600° C. to 650° C., in particular at 600° C., for 5 hours to 10 hours, advantageously 5 hours. Such treatment conditions make it possible to maximize the elongation at break of the metal part.
[0132] The present invention also relates to a method for manufacturing a metal component for manufacturing the iron-based alloy rubber product according to the present invention, the metal component manufacturing method comprising the following steps:
[0133] i- mixed basic starting materials or pre-alloyed starting materials,
[0134] ii- melting the mixture obtained in step i), advantageously in a vacuum induction muffle (VIM) furnace,
[0135] iii- optionally, homogenizing by heat treatment of the ingot obtained in step ii), advantageously at a temperature of 1240° C. for 4 hours,
[0136] iv- transforming the ingot obtained in either step ii) or step iii) by forging, in particular at high temperature, with a deformation degree advantageously ranging from 80% to 90%;
[0137] v- Recycling of the metal parts thus obtained.
[0138] In an advantageous embodiment, the method according to the invention comprises an additional step vi) of subjecting the component obtained in step v) to at least one thermal and / or physical and / or chemical treatment, advantageously chosen from a relaxation heat treatment, a hot isostatic pressing treatment, a solution treatment, an aging treatment, a finishing treatment (for example a surface modification treatment or the deposition of a coating to prevent corrosion and oxidation) and combinations of these treatments.
[0139] In an advantageous embodiment, step vi) of the method of the invention comprises a dissolution treatment at between 1050° C. and 1150° C., advantageously between 1050° C. and 1100° C., in particular at 1050° C., for 1 to 4 hours, advantageously for 1 hour, followed by an aging treatment at between 600° C. and 700° C., advantageously between 600° C. and 650° C., in particular at 600° C., for 5 to 10 hours, advantageously for 5 hours, or a direct aging treatment at between 600° C. and 700° C., advantageously between 600° C. and 650° C., in particular at 600° C., for 5 to 10 hours, advantageously for 5 hours, without dissolution. Such treatment conditions make it possible to maximize the hardness of the metal part.
[0140] In a particularly advantageous embodiment, step vi) of the method according to the invention comprises a direct ageing treatment at between 600° C. and 700° C., advantageously between 600° C. and 650° C., in particular at 600° C., for 5 to 10 hours, advantageously for 5 hours, without dissolution. Such treatment conditions make it possible to maximize the hardness of the metal part if a high-temperature heat treatment is not desired.
[0141] In another advantageous embodiment, step vi) of the method according to the invention comprises a dissolution treatment at between 900° C. and 1000° C., advantageously between 900° C. and 950° C., in particular at 950° C., for 30 minutes to 1 hour, followed by an aging treatment at between 600° C. and 700° C., advantageously between 600° C. and 650° C., in particular at 600° C., for 5 hours to 10 hours, advantageously for 5 hours. Such treatment conditions make it possible to maximize the elongation at break of the metal part.
[0142] The invention also relates to a metal part according to the invention for producing a rubber article, said metal part being produced by means of an iron-based alloy obtained from an alloy powder, said metal part being advantageously obtainable by means of the method according to the invention.
[0143] Advantageously, the metal component according to the invention is characterized in that:
[0144] - According to standard ASTM E228-17 (2017), the linear expansion coefficient between 30℃ and 200℃ is less than 3.5×10 -6 / ℃, advantageously less than 3.4×10 -6 / ℃, more preferably ≤3.3×10 -6 / ℃, and / or
[0145] - a tensile strength greater than 1000 MPa, advantageously greater than or equal to 1100 MPa, according to standard ISO 6892-1 (2019), and / or
[0146] - according to standard ISO 6507-1 (2018), its hardness HV30 is greater than 350 HV, in particular greater than 360 HV, more particularly greater than 370 HV, even more particularly greater than 375 HV.
[0147] The invention finally relates to the use of a metal part according to the invention or obtained by one of the methods according to the invention for manufacturing pneumatic or non-pneumatic tires, rubber tracks, vehicle wheels (i.e. with a mobile function) and / or parts of pneumatic or non-pneumatic tires, rubber tracks or such wheels. DETAILED DESCRIPTION
[0148] The invention will be more clearly understood on reading the following description of examples given as non-limiting guidance.
[0149] In the examples, all percentages are given on a weight basis, temperatures are in degrees Celsius, and pressures are atmospheric pressure unless otherwise indicated.
[0150] The metal components were determined by measuring the infrared absorption and thermal conductivity (LECO) of the combustion gases and by inductively coupled plasma (ICP) mass spectrometry.
[0151] Example
[0152] Various metal parts were produced consisting of the iron-based alloys whose compositions are shown in Table 1 and Table 3. The property measurements are listed in Table 2 and Table 4.
[0153] Table 1 shows Example 1 of an iron-based alloy for a metal part according to the invention strengthened by precipitation of the γ (second gamma) phase in proportions that correctly harden the alloy. A standard Invar 36 type alloy (without hardening elements, with the same level of residues) and four counter-example alloys were produced as reference.
[0154] Counterexample 1 is an iron-based alloy (Nb content less than 4.75 weight percent of all components) strengthened with a γ (second gamma) phase (whose content is lower than that of the alloy of the component according to the invention).
[0155] Counterexample 2 is an iron-based alloy strengthened by precipitation of molybdenum carbides, the Mo content of which is 3.97 (by weight percent) and the C content of which is 0.236 (by weight percent).
[0156] Counterexample 3 is an iron-based alloy strengthened by precipitation of molybdenum carbides and niobium carbides, wherein, by weight percentage, the content of Mo is 3.95, the content of Nb is 0.475, and the content of C is 0.212. These Mo, Nb and C contents are within the ranges required by patent application WO 03 / 025239, wherein the content of Mo is 1.5 to 6, the content of Nb is less than or equal to 0.5, and the content of C is 0.2 to 0.4.
[0157] Counterexample 4 is an iron-based alloy strengthened by precipitation of vanadium carbides, wherein the V content is 0.899 and the C content is 0.204. These V and C contents are very close to the Invar-V published by Nakama et al. (Metallogr. Microstruct. Anal. (2 (2013) 383-387)), wherein the V content is 0.8 and the C content is 0.203.
[0158] [Table 1]
[0159]
[0160] Table 2 shows the results of the maximum mechanical strength Rm at room temperature (according to standard ISO 6892-1:2019), the Vickers hardness HV30 at room temperature (according to standard ISO 6507-1:2018) and the coefficient of thermal expansion (CTE) measured between 30°C and 200°C according to standard ASTM E228-17 (2017) for example 1, the Invar36 reference and four counterexamples after the following operations: production of 6 kg ingots in a vacuum muffle furnace (VIM), homogenization at 1240°C for 4 hours, hot forging by punch-drawing with a deformation degree between 80% and 90%, followed by air cooling and heat treatment. The final heat treatment was different for each alloy and the results recorded are the best results obtained. Example 1 was aged at 600°C for 5 hours and then air-cooled; Counterexamples 1, 2 and 3 were precipitation aged at 650°C for 5 hours and then air-cooled; the Invar36 reference alloy was treated at 1100°C for 1 hour and then water-cooled; Counterexample 4 was dissolved at 1250°C for 1 hour and then water-cooled, and aged at 650°C for 5 hours and then air-cooled.
[0161] The γ” (second gamma) phase precipitation strengthening strategy used to strengthen the alloy enables to obtain the best hardening with limited CTE increase, compared to the reference Invar 36 and four counter-examples produced with the same residual level and equivalent transformation range. Moreover, the low hardness level of counter-example 1 (Nb content of 2.81) indicates that in order to obtain the required strengthening, the Nb content must be greater than 4.75. On the other hand, exceeding 5.5 is undesirable, as this will significantly reduce the CTE and may lead to the precipitation of undesirable phases.
[0162] Furthermore, these results show that the transformation range (especially the cold spinning or drawing step) has a strong influence on the hardening. Specifically, the Rm of counter-example 3 (whose Mo, Nb and C contents are within the range required by patent WO 03 / 025239) is equal to 795 MPa, compared to 1300 MPa for the wire produced according to patent WO 03 / 025239. The comparison of the results obtained for counter-example 4 (Rm equal to 794 MPa) with the results of the publication by Nakama et al. (Metallogr. Microstruct. Anal. 2 (2013) 383-387) (Rm after the cold transformation step is 1010 MPa) confirms this contribution of transformation to hardening.
[0163] The results show that for the equivalent transformation range, the alloy strengthening strategy with Ni content between 38.0 and 42.0, Nb content between 4.750 and 5.500, and C content between 0.010 and 0.100 achieves the best compromise between hardening and low CTE.
[0164] [Table 2]
[0165] Example 1 Reference Invar 36 Counterexample 1 Counterexample 2 Counterexample 3 Counterexample 4 Rm(MPa) 1213 453 871 795 794 A5d% 8 41 5.5 10.5 12.5 HV30 391 149 212 282 254 272 <![CDATA[CTE(×10 -6 / ℃)]]> 3.30 1.86 2.72 3.50 2.05
[0166] In another test, Example 1 was heat treated by dissolution at 1050°C for 1 h after forging, followed by water cooling, then aging at 600°C for 5 h, followed by air cooling. In this case, Rm was equal to 1129 MPa, the elongation was 15.5%, the HV30 hardness measured according to standard ISO 6507-1:2018 was 378 HV, and the CTE between 30°C and 200°C was 3.09×10 -6 / ℃. The CTE of the sample was also measured between 30℃ and 100℃, between 30℃ and 300℃, and between 30℃ and 400℃. The results were 2.47×10 -6 / ℃、5.16×10 -6 / ℃ and 7.49×10 -6 / °C. Therefore, even for the temperature range of 30°C to 400°C, the CTE is still low.
[0167] Table 3 shows the composition of Example 2 of the iron-based alloy for the metal part according to the present invention and the composition of Counter Example 5, wherein Counter Example 5 is strengthened by the precipitation of vanadium carbides produced under vacuum, then gas-atomized into powder form and screened, formed by an additive manufacturing process of powder bed laser melting with a layer thickness of 50 μm and a laser strategy of ±45° (i.e., a rotation of 90° between each consecutive layer), and then heat treated at 1050°C for 1 h, followed by air cooling, and then Example 2 is aged at 600°C for 5 h, followed by air cooling, and Counter Example 5 is aged at 650°C for 5 h, followed by air cooling.
[0168] [Table 3]
[0169] element Example 2 Counterexample 5 Fe+ impurities margin margin Ni 41.0±0.5 34.5±0.5 Co <0.400 <0.5 Cr 0.016±0.0015 <0.01 Nb 5.250±0.007 - V - 1.38±0.007 Mo - - C 0.0176±0.0015 0.2336±0.0022 N 0.0085±0.0010 0.0066±0.0009 O 0.029±0.0017 0.0187±0.0019 Mn 0.352±0.009 0.382±0.005 Si 0.340±0.0063 0.33±0.007 S 0.00154±0.0001 0.0021±0.0001 P <0.0050 <0.005
[0170] Table 4 shows the Vickers HV30 hardness obtained for Example 2 and Counter Example 5 after producing the parts by the powder bed laser melting process and the above-mentioned heat treatment.
[0171] [Table 4]
[0172] Example 2 Counterexample 5 HV30 418 266
[0173] Example 2 of an alloy produced by powder processing and additive manufacturing according to the invention confirms the hardness level obtained by a forging process of Example 1. Counterexample 5 confirms that hardening by strengthening by precipitation of vanadium carbides does not allow such high hardness levels to be obtained.
[0174] Table 5 shows the tensile strength Rm and the elongation at break A% obtained after various heat treatments of metal parts based on the alloy of Example 2. The index "H" corresponds to the test carried out on a horizontally manufactured specimen, while the index "V" corresponds to the test carried out on a vertically manufactured specimen. It can be seen that the heat treatment can be adjusted to obtain a metal part that is favorable to its hardness or elongation at break.
[0175] [Table 5]
[0176]
Claims
1. A metal part based on an iron-based alloy composition for use in the manufacture of rubber products, the iron-based alloy composition comprising, advantageously essentially consisting of, in terms of weight percentage of all components: Nickel: 38.0-42.0, advantageously 39.0-42.0; Niobium: 4.750-5.500, advantageously 5.000-5.500; Carbon: 0.010-0.100, advantageously 0.015-0.070; Cobalt: ≤ 0.400, advantageously ≤ 0.100; Chromium: ≤0.500; Silicon: ≤0.500; Manganese: ≤0.500; Iron: balance; And unavoidable impurities, calculated as a percentage by weight of all components, satisfy at least one of the following conditions: Nitrogen ≤ 0.030 wt% of all components; Oxygen ≤ 0.040 wt% of all components; Hydrogen ≤ 0.0050 wt% of all components; Sulfur ≤ 0.0150 wt% of all components; Phosphorus ≤ 0.0150 wt% of all components; Aluminum ≤ 0.100% by weight of all components; Titanium ≤ 0.100 wt% of all components; Vanadium ≤ 0.100 wt% of all components; Molybdenum ≤ 0.020 wt% of all components; Calcium ≤ 0.015% by weight of all components; Copper ≤ 0.010 wt% of all components; Magnesium ≤ 0.015 wt% of the total components.
2. The metal component according to claim 1, characterized in that The iron-based alloy contains not more than 1.00% by weight, advantageously not more than 0.50% by weight, of unavoidable impurities.
3. The metal component according to any one of claims 1 and 2, characterized in that The iron-based alloy comprises not more than 0.050% by weight of cobalt, relative to the total weight of the composition, and preferably comprises cobalt only as an unavoidable impurity.
4. The metal part according to any one of claims 1 to 3, selected from a curing mold, an injection mold and constituent elements of these molds.
5. A method for manufacturing a metal component according to any one of claims 1 to 4, comprising the following steps: A- producing an iron-based alloy powder having a composition according to the alloy composition on which the metal component is based according to any one of claims 1 to 4, according to the following steps; a) mixing basic starting materials or pre-alloying starting materials; b) melting the mixture obtained in step a), advantageously in a vacuum induction muffle furnace; c) atomizing the product obtained in step b), advantageously using nitrogen, to obtain a powder; d) screening or sieving the powder obtained in step c) to obtain a desired particle size fraction; e) recovering the powder obtained; B1 - subjecting the powder obtained in step A) to an additive manufacturing process or hot isostatic pressing to obtain the component, the additive manufacturing process advantageously being chosen from powder bed selective laser melting (LBM), electron beam melting (EBM), powder spray laser melting, for example direct additive laser structuring or direct metal deposition (DMD), and binder injection on a powder bed (MBJ), or B2—subjecting the powder obtained in step A) to a laser melting process by powder spraying such as direct additive laser structuring or direct metal deposition (DMD), followed by forging of the deposit formed from the melted powder, C- subjecting the component obtained in step B1) or in step B2) to at least one thermal and / or physical and / or chemical treatment, advantageously chosen from a relaxation heat treatment, a hot isostatic pressing treatment, if step B1) is not a hot isostatic pressing treatment, a solution treatment, an ageing treatment, a finishing treatment, such as a surface modification treatment or the deposition of a coating to prevent corrosion and oxidation, and combinations of these treatments, D- Recycling of the components thus obtained.
6. The method according to claim 5, characterized in that Step B1) is powder bed selective laser melting (LBM).
7. The method according to any one of claims 5 and 6, characterized in that Step C) comprises dissolution treatment at 1050°C to 1150°C for 1 to 4 hours, followed by aging treatment at 600°C to 700°C for 5 to 10 hours, or direct aging treatment at 600°C to 700°C for 5 to 10 hours without dissolution.
8. The method according to any one of claims 5 and 6, characterized in that Step C) comprises a dissolution treatment at 900° C. to 1000° C. for 30 minutes to 1 hour, followed by an aging treatment at 600° C. to 700° C. for 5 hours to 10 hours.
9. A method for manufacturing a metal component according to any one of claims 1 to 4, comprising the following steps: i. Mixed base starting materials or pre-alloyed starting materials; ii. melting the mixture obtained in step i), advantageously in a vacuum induction muffle furnace, iii. optionally, homogenizing by heat treating the ingot obtained in step ii), iv. transforming the ingot obtained in any one of steps ii) and iii) by forging, v. Recycling of the components thus obtained, vi. Preferably, the component obtained in step v) is subjected to at least one thermal and / or physical and / or chemical treatment, which is advantageously selected from a relaxation heat treatment, a hot isostatic pressing treatment, a solution treatment, an aging treatment, a finishing treatment and a combination of these treatments, the finishing treatment being, for example, a surface modification treatment or deposition of a coating to prevent corrosion and oxidation.
10. The method according to claim 9, characterized in that Step vi) comprises dissolution treatment at 1050°C to 1150°C for 1 to 4 hours, followed by aging treatment at 600°C to 700°C for 5 to 10 hours, or direct aging treatment at 600°C to 700°C for 5 to 10 hours without dissolution.
11. The method according to claim 9, characterized in that Step vi) comprises a dissolution treatment at 900° C. to 1000° C. for 30 minutes to 1 hour, followed by an aging treatment at 600° C. to 700° C. for 5 hours to 10 hours.
12. The metal part according to any one of claims 1 to 4 or obtained by the method according to any one of claims 5 to 11, characterized in that: According to standard ASTM E228-17 (2017), the linear expansion coefficient between 30℃ and 200℃ is less than 3.5×10 -6 / ℃, and / or According to standard ISO 6892-1:2019, its tensile strength is greater than 1000 MPa, and / or According to standard ISO 6507-1:2018, its hardness HV30 is greater than 350HV.
13. Use of a metal part according to any one of claims 1 to 4 or obtained by a method according to any one of claims 5 to 11 for the manufacture of a pneumatic or non-pneumatic tyre, a track, a vehicle wheel and / or a part of a pneumatic or non-pneumatic tyre, a track or such a wheel.
Citation Information
Patent Citations
Tyre tread comprising zigzag incisions and blades for moulding such incisions
EP1758743A1
Press die for molding sipe blade and method of making the press die
US20020139164A1
Invar alloy wire excellent in strength and turning characteristics and method for production thereof
WO2003025239A1